EVALUASI KINERJA KEUANGAN MENGGUNAKAN ANALISIS RASIO KEUANGAN (Studi pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Andika Hidayatullah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims at evaluating the financial performance of cigarette companies listed in the Indonesia Stock Exchange. The financial ratios that are used as analyzing tools are liquidity ratio, assets management ratio, leverage ratio, profitability ratio, and market value ratio. The samples used in this research are companies listed in the Indonesia Stock Exchange during the period of 2011-2015.The results of this research show that PT. Gudang Garam, Tbk. were able to manage liquid assets that makes PT. Gudang Garam, Tbk. can fulfill companies liability and makes PT. Gudang Garam, Tbk. has a strengths on liquidity ratio. PT. Gudang Garam, Tbk. is not funded companies asset with a large amount of debt, that makes PT. Gudang Garam, Tbk. has a strengths on leverage ratio. PT. HM Sampoerna, Tbk. has a strengths on assets management ratio, that makes PT. HM Sampoerna, Tbk. has a high profitability ratio and high market value ratio.Keywords: Financial Performance, Liquidity Ratio, Assets Management Ratio, Leverage Ratio, profitability ratio, market value ratio